How do Chinese people perceive their healthcare system? Trends and determinants of public satisfaction and perceived fairness, 2006-2019 - Yishan Zhu; Yuanyuan Li; Ming Wu; Hongqiao Fu (BMC, 2022)
Abstract Background The public's perception of the health system provides valuable insights on health system performance and future directions of improvement. While China's health care reform was a response to people's discontent in the health care system due to the lack of accessibility and affordability, little is known on changes in public perception of China's health system. This paper examines trends in public perception of the health system between 2006 and 2019 and assesses determinants of public perception in China's health system. Methods Seven waves of the China Social Survey, a nationally representative survey, were used to examine trends in public satisfaction with health care and perceived fairness in health care. Chi-square tests were used to examine differences across waves. Logistic regression models were used to explore determinants of public perception, including variables on sociodemographic characteristics, health system characteristics, and patient experience. Results Satisfaction with health care increased from 57.76% to 77.26% between 2006 and 2019. Perceived fairness in health care increased from 49.79% to 72.03% during the same period. Both indicators showed that the major improvement occurred before 2013. Sociodemographic characteristics are weakly associated with public perception. Financial protection and perceived medical safety are strongly associated with public perception, while accessibility is weakly associated with public perception. Patient experience such as perceived affordability and quality in the last medical visit are strongly associated with public perception of the health care system, while the accessibility of the last medical visit shows no impacts. Conclusion Public satisfaction on health care and perceived fairness in health care in China improved over 2006-2019. The main improvement occurred in accordance with huge financial investments in public health insurance before 2013. Financial protection and perceived quality play significant roles in determining public perception, whereas accessibility and sociodemographic characteristics have limited influence on people's perception of China's health system. To achieve higher satisfaction and a higher sense of fairness in health care, China's health system needs to continue its reforms on hospital incentives and integrated delivery system to control health expenditure and improve health care quality.